Post covid-19 pandemic perception and purchase behaviour of Malaysians towards consumer goods - Fong, Eng Cheong (2023)
In this study, a correlation and regression analysis were conducted to explore the relationships between attitude, subjective norm, perceived behavior control, and intention to buy consumer goods. The results of the correlation analysis showed that attitude, subjective norm, and perceived behavior control are positively correlated with intention to buy consumer goods. However, attitude was weakly and non-significantly correlated with intention to buy consumer goods. The regression analysis further revealed that attitude, subjective norm, and perceived behavior control are significant predictors of intention to buy consumer goods. The regression model accounted for 20.4% of the variance in intention to buy consumer goods, with perceived behavior control having the strongest effect on intention to buy. These findings suggest that marketers and retailers should pay attention to consumers' attitudes, subjective norms, and perceived behavior control when developing marketing strategies and campaigns aimed at increasing consumers' intention to buy their products. Emphasizing the benefits and ease of buying the product, as well as highlighting the social approval and norms surrounding the product, may help increase consumers' intention to buy.